Implementasi Literasi Digital Pada Pembelajaran Fikih Di MAN 1 Aceh Barat - Mustika Ayu; Iin Kandedes; Sururin Sururin (Al-Ulum: Jurnal Pendidikan Islam, 2022)
This research aims to describe the implementation of digital literacy in learning. Fiqh chapter "Organization of bodies" at MAN 1 Aceh Barat. This research method uses a qualitative approach, which is sourced from primary and secondary data. Sources of primary data obtained from interviews with the principal, 3 Fiqh teachers, students and the results of observations. While secondary data sources were obtained from documentation such as manuscripts, archives, and photos related to the implementation of digital literacy activities in the Jurisprudence learning process in the chapter "Organization of Bodies" at MAN 1 Aceh Barat. The results of this study indicate the implementation of digital literacy in the Jurisprudence learning chapter "Organization of bodies" in class X Religion, MIPA 1 and MIPA 3 through three aspects, namely: (1) Access learning content, through LMS (learning management system) by utilizing e-modules. which can be accessed via flibook, youtube. (2) Digital literacy as a learning tool, which utilizes website-based learning media that invites students to explore various sites related to the material "Organization of Bodies". (3) Communication tool between and teachers by utilizing the platform; whatsapp group, and zoom meeting.